Surgery in Jehovah's Witnesses - Smith, Earl Belle (1986)
Surgical experiences are described with 96 adult patients who professed and practiced the Jehovah's Witness faith and whose refusal of blood transfusions and blood-related products created problems in circulatory fluid volume, cardiorespiratory exchanges, cerebral, hepatic, and renal metabolic processes, and wound healing. The surgical mortality rate was representative and the surgical complication rate was excessive. The most frequent complications (93.5 percent) were wound-healing problems.